PERANCANGAN RANGKAIAN BOOSTER PADA MATA PELAJARAN ELEKTRONIKA DI SMK NEGERI 2 TANJUNGBALAI - Muhammad Amin; Muhammad Sabir Ramadhan; Ricki Ananda (RJOCS (Riau Journal of Computer Science), 2017)
Learning methods and models is one way used by teachers or educators to deliver teaching materials to students or the learner. The use of inappropriate methods or instructional media is perceived to be one of the students' barriers to receiving lessons learned by teachers. The use of learning methods and models with visual aids and practice is very effective, because students can directly recognize the form of components or media used directly. For the material used, design a series of booster converter to turn on 5 watt lights, with 3.7 V battery inputs using booster, the input can be on